2020
DOI: 10.1149/2162-8777/abcf13
|View full text |Cite
|
Sign up to set email alerts
|

Contamination Mechanism of Ceria Particles on the Oxide Surface after the CMP Process

Abstract: The contamination behavior of ceria particles (50 and 100 nm) with oxide surfaces at pH 4 and 8 was studied using dipping and polishing conditions. Higher contamination at pH 4 than pH 8 was observed for dipping cases. In contrast, pH 8 conditions produced higher contamination than pH 4 for polishing cases. The difference in the contamination between dipping and polishing could be attributed to electrostatic attraction and chemical bonding. During polishing, weak or no chemical bonding may occur at pH 4, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Considering that K9 glass has an electronegative surface charge (negative zeta potential), opposite surface charge will lead to the adhesion of calcined particles to the K9 surface by electrostatic attraction, which is helpful to improve the removal rate. 29,30 The particle size distribution measurement showed that D 90 of the calcined products was remarkably increased with the rising of calcination temperature, resulting in the broadening of the particle size distribution (R values). This may be because with the increase of calcination temperature, fusion occurred not only between primary nanocrystals, but also between octahedrons, forming particle agglomerates.…”
Section: Resultsmentioning
confidence: 99%
“…Considering that K9 glass has an electronegative surface charge (negative zeta potential), opposite surface charge will lead to the adhesion of calcined particles to the K9 surface by electrostatic attraction, which is helpful to improve the removal rate. 29,30 The particle size distribution measurement showed that D 90 of the calcined products was remarkably increased with the rising of calcination temperature, resulting in the broadening of the particle size distribution (R values). This may be because with the increase of calcination temperature, fusion occurred not only between primary nanocrystals, but also between octahedrons, forming particle agglomerates.…”
Section: Resultsmentioning
confidence: 99%
“…Both pseudoternary phase equilibria diagrams of the CeO 2 –MnO 2 –Fe 2 O 3 –S and FeS–MnSO 4 –Fe 2 O 3 –CeO 2 system (Figures S7) suggested that Ce 2 (SO 4 ) 3 was found to be a favorable stable phase in the synergistic process. Binding energy at 886.5, 890.2, 893.9, and 897.9 eV in the XPS spectra (Figures S6D) and the characteristic peaks at 1120.8 cm –1 in the Raman spectrum (Figure S8) were assigned to Ce­(III) 3d 5/2 and SO 4 2– , respectively, ,− which further confirmed the transformation of CeO 2 as Ce 2 (SO 4 ) 3 . However, the orthogonal experimental results revealed that when the calcinating temperature was over 400 °C, lower leaching efficiency of Ce was obtained, indicating the further transformation of Ce 2 (SO 4 ) 3 with the raised temperature.…”
Section: Resultsmentioning
confidence: 58%
“…Different removal mechanisms such as undercut/etching, dissolution, bond rupture, and electrostatic interactions have been reported for ceria removal from oxide wafers. 9,20,[25][26][27][28] To investigate the mechanism of ceria removal from oxide wafers during scrubbing, we focused on undercut/etching and electrostatic interaction phenomena. No significant etching of the oxide was observed with different pH cleaning solutions (results are not reported here), which indicates that undercutting is not a major factor during brush scrubbing at any pH condition.…”
Section: Resultsmentioning
confidence: 99%